Pengetahuan Siswi SMA tentang Pemeriksaan Payudara Sendiri berhubungan dengan Upaya Pencegahan Kanker Payudara - Rahmi; Eka Santosa; Novi Enis Rosuliana; Endah Sulistiyani; Ni Made Sumartyawati (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2024)
Introduction: According to WHO, every year the number of ca mammae sufferers increases by around 12 million and 7.6 million of them die. The latest survey in the world shows that every 3 minutes someone finds breast cancer and every 11 minutes someone dies from breast cancer.  Purpose: The aim of this research is to determine the relationship between high school students' knowledge about breast self-examination and efforts to prevent breast cancer at SMAN 1 Labuapi, West Lombok.  Method: Quantitative research method with a descriptive correlation design using a cross sectional approach. The sample in the study was 34 respondents taken by total sampling. Data collection uses questionnaire sheets, data analysis uses Spearmen Rank.  Results: Based on data analysis using Spearman Rank, p value = 0.000 < 0.05, meaning there is a relationship between female students' knowledge about breast self-examination and efforts to prevent breast cancer at SMAN 1 Labuapi, West Lombok. Suggestion: Young women can better understand and pay attention to breast self-examination and can use it as a medium for obtaining health information regarding breast cancer prevention.